FORMULATION AND OPTIMIZATION OF DOMPERIDONE-LOADED LIQUID SNEDDS: CHARACTERIZATION AND IN-VITRO EVALUATION - Sara Rassol; Adnan Burhan Qader (Science Journal of University of Zakho)
This research concentrated on developing and optimizing domperidone-loaded Self- nanoemulsifying drug delivery system (SNEDDS) to enhance solubility, stability, and availability. Domperidone (DOM), a lipophilic drug characterized by its limited solubility in water, was integrated into SNEDDS formulations utilizing a range of oils, surfactants, and cosurfactants. Solubility studies indicated that orange oil exhibited the highest solubility for DOM at (47.94 mg/mL ± 0.085) against oils, Cremophor EL among surfactants, and Transcutol HP against cosurfactants. The solubility enhancement can be attributed to the formation of nanoemulsions, which effectively diminish particle size and enhances surface area, leading to improved dissolution and accelerated absorption.  The optimization of the formulation was conducted utilizing a pseudo-ternary phase diagram, twelve successful formulations were evaluated and characterized for self-emulsification, stability, and drug release. In-vitro characterization demonstrated that F1 formula (Orange oil+ Cremophor EL+ Transcutol HP) using (2:8, oil: S.mix ratio) released DOM at rates up to 3.7 times greater than those of commercial products. The rapid emulsification times, ranging from (13.75 ± 0.528 to 32.17 ± 1.193 seconds), consistent droplet sizes, and a low PDI (0.28 ± 0.03 to 0.68 ± 0.2) have significantly improved bioavailability